Frames of reference for eye–head gaze shifts evoked during frontal eye field stimulation. Issue 11 (13th March 2013) - Monteon, Jachin A.; Wang, Hongying; Martinez‐Trujillo, Julio; Crawford, J. Douglas
Abstract: The frontal eye field (FEF), in the prefrontal cortex, participates in the transformation of visual signals into saccade motor commands and in eye–head gaze control. The FEF is thought to show eye‐fixed visual codes in head‐restrained monkeys, but it is not known how it transforms these inputs into spatial codes for head‐unrestrained gaze commands. Here, we tested if the FEF influences desired gaze commands within a simple eye‐fixed frame, like the superior colliculus (SC), or in more complex egocentric frames like the supplementary eye fields (SEFs). We electrically stimulated 95 FEF sites in two head‐unrestrained monkeys to evoke 3D eye–head gaze shifts and then mathematically rotated these trajectories into various reference frames. In theory, each stimulation site should specify a specific spatial goal when the evoked gaze shifts are plotted in the appropriate frame. We found that these motor output frames varied site by site, mainly within the eye‐to‐head frame continuum. Thus, consistent with the intermediate placement of the FEF within the high‐level circuits for gaze control, its stimulation‐evoked output showed an intermediate trend between the multiple reference frame codes observed in SEF‐evoked gaze shifts and the simpler eye‐fixed reference frame observed in SC‐evoked movements. These results suggest that, although the SC, FEF and SEF carry eye‐fixed information at the level of their unit response fields, this information is transformed differently in their output projections to the eye and head controllers. Abstract : The frontal eye fields (FEF), located in prefrontal cortex, participate in the transformation of visual signals to gaze motor commands. We stimulated the FEF in head‐unrestrained monkeys to see whether this produces gaze shifts toward eye‐fixed goals, or toward goals defined in other frames. Consistent with the FEF's intermediate placement within high‐level gaze circuitry, we found that the frames for its motor output varied site‐by‐site, mainly within the continuum between eye and head frames.